Vapor–Liquid Equilibrium Study of LiBr + H2O and LiBr + CaCl2 + H2O Systems - Wang, Huinan; Chen, Hongfei; Chen, Wanhao; Sun, Haoran; Xu, Xianzhen (Frontiers in Chemistry, 2020)
Vapor–liquid equilibrium (VLE) data and modelling for LiBr+H2O and LiBr+CaCl2+H2O are reported in this paper. This work focuses on the experimental determination of boiling point for LiBr+H2O and LiBr+CaCl2+H2O solutions with vapor pressure between 6 and 101.3 kPa, the total molality of salt ranging from 0 to 21.05 mol•kg-1. The procedures were carried out in a computer-controlled glass apparatus. The relationship between boiling point and saturated vapor pressure is obtained, and the modified NRTL model is used to correlate and predict the VLE. By correlation of the data (literature and experimental) for LiBr+H2O and LiBr+CaCl2+H2O, the parameters are obtained. We compared the results with the ElecNRTL model and Pitzer’s model. The parameters for LiBr+H2O, CaCl2+H2O and LiBr+CaCl2+H2O systems can be successfully used to calculate and predict the VLE data.